1980
DOI: 10.1002/1097-0142(19800615)45:12<3012::aid-cncr2820451223>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of ulceration of cutaneous melanoma

Abstract: Ulceration of a cutaneous melanoma on microscopic sections is an adverse prognostic finding. The five-year survival rate is reduced from 80% for non-ulcerated melanomas to 55% in the presence of ulceration for Stage I melanoma patients and from 53 to 12% for Stage II melanoma patients (P less than 0.001). As a group, ulcerated lesions are thicker and more likely to have a nodular growth pattern. However, survival rates were still worse for ulcerated melanomas when matched with nonulcerated lesions for thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
99
0
14

Year Published

1982
1982
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(125 citation statements)
references
References 15 publications
12
99
0
14
Order By: Relevance
“…The survival profiles for the four sex/ulceration subgroups clearly demonstrated that increasing tumour thickness reduced survival prospects in all four groups. Ulceration is a significant predictive factor in many studies that have controlled for tumour thickness (Balch et al, 1978(Balch et al, , 1980Van der Esch, 1981;Day et al, 1982b;Urist et al, 1984;Shaw et al, 1985;O'Brien et al, 1991;Andersson et al, 1993;Langford et al, 1993;MacKie et al, 1995) and even retains significance in patients with lymph node metastasis (Balch et al, 1980). Male sex has been associated with poorer prognosis in most studies of head and neck melanoma (Ballantyne, 1970;Fitzpatrick et al, 1972;Hansen and McCarten, 1974;Gussack et al, 1983;Cox et al, 1987;O'Brien et al, 1991;Langford et al, 1993;Ringborg et al, 1993;Andersson et al, 1993), although some studies report no sex difference (Catlin, 1966;Knutson et al, 1972;McGovern et al, 1980) and one reported a better prognosis in men (Southwick et al, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…The survival profiles for the four sex/ulceration subgroups clearly demonstrated that increasing tumour thickness reduced survival prospects in all four groups. Ulceration is a significant predictive factor in many studies that have controlled for tumour thickness (Balch et al, 1978(Balch et al, , 1980Van der Esch, 1981;Day et al, 1982b;Urist et al, 1984;Shaw et al, 1985;O'Brien et al, 1991;Andersson et al, 1993;Langford et al, 1993;MacKie et al, 1995) and even retains significance in patients with lymph node metastasis (Balch et al, 1980). Male sex has been associated with poorer prognosis in most studies of head and neck melanoma (Ballantyne, 1970;Fitzpatrick et al, 1972;Hansen and McCarten, 1974;Gussack et al, 1983;Cox et al, 1987;O'Brien et al, 1991;Langford et al, 1993;Ringborg et al, 1993;Andersson et al, 1993), although some studies report no sex difference (Catlin, 1966;Knutson et al, 1972;McGovern et al, 1980) and one reported a better prognosis in men (Southwick et al, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…The work of Clark, Breslow, Balch and their associates in the past decade has greatly extended the volume of useful information, often of considerable prognostic significance, which can be obtained from light-microscopic examination of appropriate blocks of paraffin-embedded tissue (Clark et al, 1969;Breslow, 1977;Breslow & Macht, 1978;Balch et al, 1978Balch et al, , 1979Balch et al, , 1980. Clark has suggested that there are several different histogenetic precursors or lateral growth phases of the pre-invasive epidermal component of cutaneous malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…By convention we measure the size of any ulcer. 93 The five year survivorship in Stage I-II melanomas decreased from 80 to 55% in the presence of ulceration and for Stage III melanomas dropped from 53 to 12%. The majority of melanomas greater than 4.0 mm in thickness are ulcerated.…”
Section: Ulcerationmentioning
confidence: 99%